Addressing the endogeneity of slack in Phillips Curves - Max-Sebastian Dovì; Gerrit Koester; Christiane Nickel (European Central Bank (ECB), 2021)
Endogeneity of the labour market slack in reduced-form Phillips Curves (PCs) is usually addressed either by including proxies for omitted supply shocks, or by using instrumental variables. Using the Kiviet (2020) Kinky Least Squares estimator, we find evidence that supply-shock proxies should not be omitted from PCs, and that many popular instrumental variables seem to be invalid. We estimate a standard backward-looking wage Phillips Curve by Kinky Least Squares and find that unless a large negative correlation between the slack variable and the error term is assumed, the coefficient of the slack variable is significantly negative.
Keywords: C1; E3; 330; Phillips Curves; instrument-free inference; limited-information inference